Application of the Tabarak Method in Learning Maharah Istima' at Level 7 during the Covid-19 Pandemic in Sidoarjo Regency: Penerapan Metode Tabarak dalam Pembelajaran Maharah Istima’ Di Level 7 pada Masa Pandemi Covid-19 di Kabupaten Sidoarjo - Syahra, Fillah Audy; Anwar, Najih (Indonesian Journal of Education Methods Development, 2022)
This article aims to determine the application of the Tabarak method in learning maharah istima' at level 7 during the Covid-19 pandemic at the Markaz al-Firdaus International Foundation in Sidoarjo Temple. This research uses a case study approach in which data is obtained from a detailed study of a single background, single subject, or particular event. The results showed that the implementation of the Tabarak method in learning maharah istima' at level 7 during the Covid-19 pandemic at the Markaz al-Firdaus International Foundation in Sidoarjo Temple continued using Zoom, WA and Google Form media.